Rethinking globalization, English and multilingualism in Thailand: a report on a five-year ethnography - Lee, Hugo Yu-Hsiu (Penerbit Universiti Kebangsaan Malaysia, 2019)
The starting point of this paper is to the development of a relatively panoramic account of English and multilingualism in Thailand, illuminating the relationships among powers (trends), individuals and groups and their multilingual practices. Most previous studies draw upon arguments from the traditional monocentric model of nation-state multilingualism. Surprisingly, little is known about the polycentric forces influencing multilingual distributions. Methodologically, large-scale data sets are gathered through literature, documents, questionnaires, interviews and observing actual language behaviors. The ethnographic data gathered are analyzed through content analysis conventions. Challenging Smalley’s nationalist model, the central thesis of this paper is to present an alternative path, a polycentric model, to better understand Thailand’s multilingualism. There is a lack of adequate evidence within and across Thailand to show the existence of a universal and coherent hierarchy connecting different layers of language users. As such, this paper argues that Smalley’s universal hierarchy/dominance model has to compete with alternative models termed a ‘multiarchy’ or ‘multiarchies’ (a portmanteau of “multiple hierarchies”) where parallel language hierarchies co-exist with the orthodox one.